Value of Beauty in Ancient Philosophy - Jankauskas, Skirmantas (Problemos, 1991)
An attempt is made to trace back the origins of the aesthetics in ancient philosophy from Thales to Socrates. Plato’s conception of the ancient philosophy (“Symposion”) is taken as a key of research. Parallels between the grades of Plato’s “way to Beauty” and the stages of ancient philosophy itself are pointed out. Finally, the general inference about the value of beauty as the direct mover of ancient philosophy is drawn out.